URGENSI KONSEP AMONG KI HAJAR DEWANTAR SEBAGAI UPAYA DEKONTRUKSI TOXIC RELATIONSHIP DI KALANGAN MAHASISWA - Izzatun Nikmah; Yumna Khairani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The phenomenon of toxic relationships among university students has exhibited an increasing trend in recent years, characterized by relational patterns marked by excessive control, emotional manipulation, and communicative inequality. This study aims to analyze the urgency of implementing Ki Hajar Dewantara’s Sistem Among as a conceptual framework for the deconstruction of such toxic relational patterns. The research employs a qualitative method with a library research approach, involving the analysis of various scientific articles and contemporary published documents. The findings reveal that toxic relationships among students manifest through domination, transgression of personal boundaries, and the diminishment of psychological autonomy. The Sistem Among concept, embodied in its educational trilogy—Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani—offers a relational paradigm grounded in the core principles of liberty, exemplary conduct, and empowerment. The deconstruction of toxic relationships through the lens of Sistem Among is achieved by transforming relational dynamics from asymmetrical power structures into equitable, mutually autonomous associations founded upon the respectful recognition of every individual’s innate character. This study recommends the internalization of the values inherent in Sistem Among within relational literacy programs at higher education institutions, serving as both a preventive and curative strategy to mitigate the occurrence of toxic relationships.